1997
DOI: 10.1111/j.1399-302x.1997.tb00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase isoform activities released by human neutrophils in response to dental and periodontal bacteria

Abstract: Myeloperoxidase is an enzyme released by polymorphonuclear leukocytes which has been used, experimentally, as an indicator of periodontal disease activity when measured in gingival crevicular fluid. There are three myeloperoxidase isoforms: MPO I, MPO II and MPO III. We examined the activities of myeloperoxidase isoforms released by neutrophils in response to serum-opsonized Actinobacillus actinomycetemcomitans, Haemophilus aphrophilus, Eikenella corrodens, Capnocytophaga sputigena and Streptococcus sanguis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
(39 reference statements)
0
15
0
2
Order By: Relevance
“…Azurophil granule exocytosis is tightly controlled, and only 20% of the granule pool is mobilized, since release of proteases from the cell will damage host tissues (24,50). As with MMPs, elevated levels of MPO are present in the gingival crevicular fluid of periodontitis patients, indicating that oral pathogens can trigger azurophil granule exocytosis (51,52). In this study, we found that P. stomatis challenge of human neutrophils triggered both a timedependent and a concentration-dependent release of MPO.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Azurophil granule exocytosis is tightly controlled, and only 20% of the granule pool is mobilized, since release of proteases from the cell will damage host tissues (24,50). As with MMPs, elevated levels of MPO are present in the gingival crevicular fluid of periodontitis patients, indicating that oral pathogens can trigger azurophil granule exocytosis (51,52). In this study, we found that P. stomatis challenge of human neutrophils triggered both a timedependent and a concentration-dependent release of MPO.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we found that P. stomatis challenge of human neutrophils triggered both a timedependent and a concentration-dependent release of MPO. Similarly, F. nucleatum, P. gingivalis, and T. denticola can induce the release of elastase from neutrophils, and Aggregatibacter actinomycetemcomitans can induce MPO release (40,51,52). In contrast, we recently showed that the newly recognized periodontal pathogen Filifactor alocis did not induce azurophil granule release even at a high multiplicity of infection (53).…”
Section: Discussionmentioning
confidence: 99%
“…1 The enzyme is largely expressed in polymorphonuclear neutrophils and, therefore, the highest levels of enzyme activity were found at sites with increasing gingival inflammation. The function to combat pathogenic oral bacteria may protect from infection, on the other hand activated neutrophils promote cell destruction and MPO activity measurements have been used as predictors of periodontal disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Componentes dos SPS, a PO e a MPO salivares foram amplamente estudados no DM (Güven et al, 1996;Wiersna et al, 2008;Gorudko et al, 2012) e na DP (Miyasaki;Nemirovskly;Gonçalves et al, 2008;Meschiari et al, 2013). Os resultados do presente estudo estão consistentes com os estudos de Smith et al (1984), Güven et al (1996), Sakamoto et al (2008) (Gonçalves et al, 2008).…”
Section: Resultados Demográficosunclassified
“…A PO e a MPO foram amplamente estudados na saliva no DM (Guven et al, 1996;Wiersna et al, 2008;Gorudko et al, 2012) e na DP (Miyasaki;Nemirovskiy, 1997;Gonçalves et al, 2008;Meschiari et al, 2013). Foi relatado um aumento da atividade SPO em gengivite experimental, uma vez que ocorre uma exsudação de leucócitos através do sulco gengival para a saliva, diminuindo sua atividade após higiene oral normal (Smith et al, 1984).…”
Section: Saliva E O Sistema Peroxidaseunclassified